Non-prescription medicine mobile healthcare application: Smartphone-based software design and development review - Orawit Thinnukool (2018)
The challenge of this research is to answer the question of what the real need of users regarding the development of a smartphone-based software for healthcare application. This study aimed to develop the nonprescription drugs mobile health application (NMMHA) to support users in the initial medication. The application has been released to evaluate tested its usability and satisfaction. To ensure the NMMHA is going to perform well, a survey has been conducted to collect data about the opinions of two groups of responders (pharmacists and general people). An attitude test and statistical analysis have also been accomplished for both groups to determine the differentiation between the two groups. The impressive results indicate that the group of general peoples tend to use the application more than the group of pharmacists, whereas the overall attitude test results of the two groups are not different.